Self-foldable origami reflector antenna enabled by shape memory polymer actuation. (23rd September 2020) - Jape, Sameer; Garza, Milton; Ruff, Joshua; Espinal, Francisco; Sessions, Deanna; Huff, Gregory; Lagoudas, Dimitris C; Peraza Hernandez, Edwin A; Hartl, Darren J
Abstract: This paper presents the design, fabrication, and characterization of a self-foldable Active Origami Reflector Antenna (AORA) of parabolic form. Self-folding of the AORA is enabled by smooth uncreased folds composed of shape memory polymer (SMP) composites. Design methods for origami with smooth folds are applied to determine the shape and fold pattern of a planar sheet that can be folded to reach the parabolic antenna shape. A proof-of-concept prototype of the AORA is fabricated and self-folding of the AORA driven by thermal actuation of the SMP composite folds is demonstrated. The far-field electromagnetic (EM) characteristics of the AORA prototype are investigated through numerical simulations and experimental measurements in an anechoic chamber. A design-of-experiment study is conducted to investigate the effects of the antenna shape parameters on its EM characteristics such as far-field antenna gain and beamwidth, and to compare the performance of the AORA to that of equivalent smooth and faceted parabolic reflectors. Applications of the AORA include high-gain directional radio telescopes and satellite telecommunication.